1961
DOI: 10.1143/ptp.25.803
|View full text |Cite
|
Sign up to set email alerts
|

Exact Treatment of the Bound State Problems in the Non-Relativistic Quantum Field Theory

Abstract: An exact equation for the bound state of nucleons in the static neutral scalar model is obtained by using the field equation for Heisenberg operator and the method of canonical transformaticn. The formulation of the eigenvalue problem is completed by the analyticity consideration. In particular, a boundary condition at -r=O ( -i-r being the "negative imaginary" relative time) turns out that the derivative of the "wave function" with respect to -r must be zero at -r=O. The abnormal wlutions exist in this case a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1965
1965
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 6 publications
(8 reference statements)
1
12
0
Order By: Relevance
“…In Section 4 we study the interaction between two nucleons in the model by Yukawa. It has turned out that our method readily leads to an exact result which reproduces those obtained by N. Mugibayashi [12] with the help of a much more laborious method (using Feynman diagrams, see [13]).…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…In Section 4 we study the interaction between two nucleons in the model by Yukawa. It has turned out that our method readily leads to an exact result which reproduces those obtained by N. Mugibayashi [12] with the help of a much more laborious method (using Feynman diagrams, see [13]).…”
Section: Introductionsupporting
confidence: 53%
“…One way to solve this problem is our method of approximate pair correlations which enables one to solve the problem exactly. It is convenient to base ourselves on paper [12] where an exact equation for the transition amplitude is obtained. The main aim of this section is to test once again the quality of our approximation on various models.…”
Section: Investigation Of Yukawa Modelmentioning
confidence: 99%
“…Wick suggested that these solutions could be an artefact due to the ladder approximation, and would disappear if the higher-order irreducible graphs could be included [3]. Mugibayashi showed however that the abnormal solutions remain present in the exact static model [7], which is simple enough to be completely solved. Recently, the conclusions of Mugibayashi were questioned by Jallouli and Sazdjian [8], so that the road to Wick's interpretation is open again.…”
Section: Introductionmentioning
confidence: 99%
“…In this connection the exact static model was analyzed by Mugibayashi [9]. Using hamiltonian formalism he derived a second order differential equation that he identified with the Bethe−Salpeter equation.…”
mentioning
confidence: 99%